Alternative Photosynthetic Electron Transfers and Bleaching Phenotypes Upon Acute Heat Stress in Symbiodinium and Breviolum spp. (Symbiodiniaceae) in Culture - Dang, Kieu Van; Pierangelini, Mattia; Roberty, Stéphane; Cardol, Pierre (Frontiers in Marine Science, 2019)
The breakdown of the symbiosis between cnidarians and Symbiodiniaceae often occurs upon periods of elevated sea surface temperature and gives rise to bleaching events that affect coral reefs worldwide. In the prevailing model explaining the cellular mechanisms of bleaching, an impairment of photosynthesis would be responsible for light-dependent generation of toxic reactive oxygen species and ultimately for death of symbionts and/or host cells. In some Symbiodiniaceae species, alternative photosynthetic electron flows (AEF) have been documented to occur upon a shift to high temperature, possibly contributing to photoprotection and to the balance of energetic ratio between photoproduced ATP and NADPH. By using a combination of in vivo spectrofluorimetric and oximetric techniques, we studied the capacity for electron rerouting towards oxygen and cyclic electron flow around photosystem I in nine Symbiodiniaceae species belonging to Symbiodinium and Breviolum genera upon a shift from 25°C to 33°C. CEF capacity was determined as the kinetic of PSI primary donor P700 re-reduction in the presence of DCMU, a PSII inhibitor. An active oxygen uptake in light was estimated by comparing net oxygen evolution and relatove electron transport rate of PSII at different light intensities. Among strains that showed elevated capacity for both AEF, some were thermotolerant while others were thermosensitive. Conversely, in some thermotolerant strains, capacities for these AEF were low upon heat stress. Our results thus indicate that a high CEF capacity and/or a high ability to reroute electrons towards O2 are not sufficient to confer thermal resistance of isolated Symbiodiniaceae.